Beyond control: the criminalization of African asylum seekers in Israel. Issue 1 (2nd January 2020) - Orr, Zvika; Ajzenstadt, Mimi
ABSTRACT: This article analyzes the discursive process of criminalization of African asylum seekers in Israel. The Israeli case illuminates the way that marginalized social groups are constructed as a criminal threat, thus becoming a focal point of moral panic. Using content analysis, in-depth interviews and observations, we assert that the criminalization of asylum seekers is facilitated by their portrayal as 'infiltrators' who are beyond state control. State authorities' ostensible inability to keep asylum seekers under surveillance is dialectically constructed along two main axes: the private space axis and the public space axis. On the private space axis, the asylum seekers are portrayed as unidentified people living beyond the authorities' field of vision whose largely unreported criminality is directed against vulnerable asylum seeker women and children in the private sphere. At the same time, asylum seekers are portrayed as a prominent, faceless and animalistic presence in public space, a presence that breaches physical-spatial borders as well as social-cultural boundaries, thereby undermining the social order. Thus, asylum seekers are viewed as conspicuously invisible. This rhetoric connects border violation with criminal activity; emphasizes the pent-up potential for violence by asylum seekers; and blurs the lines between criminal threat and security threat.